Now I don’t know how to do this but I would recommended a tutor for you
Answer:
a = 5
Step-by-step explanation:
According to the factor theorem, if x + 2 is a factor, then by dividing the polynomial by the binomial, we are meant not to have a remainder
In this case, the remainder would be zero
So, if we set the binomial equals zero and substitute the x-value into the polynomial, we are supposed to have 0
So we have this as;
x + 2 = 0
x = -2
-2^3 -2(-2)^2 -2(a) + 6 = 0
-8-8-2a + 6 = 0
-16 + 2a + 6 = 0
2a -10 = 0
2a = 10
a = 10/2
a = 5
Answer:
False. See explanation below.
Step-by-step explanation:
False
A simple random sample "is a subset of a statistical population in which each member of the subset has an equal probability of being chosen"
In other words that means in order to apply a random sampling we need to ensure that we have the same probability of inclusion for every possible element of the population of interest.
And for this case a collection of any numerical information is not referred as random sampling since we don't know if these scores are representative of the population of interest.
And we don't know if this information is obtained using any sampling frame or sampling methodology.
Answer:
9
Step-by-step explanation:
cross multiply 7/63 by 1/x
so, multiply 7 by x and 63 by 1
you get 63=7x
divide by 7 on both sides and you get 9
Answer:
N= -14
Step-by-step explanation:
first you add 16 to both sides, then -30 + -16 = -14